Analisa Location Quotient (LQ) Sektor Akomodasi dan Penyediaan Makan Minum di Kabupaten/Kota Se-Sumatera Barat - Masruqi Arrazy (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
Tourism is one of the service and service industry activities that is a mainstay of Indonesia in the context of increasing the country's foreign exchange in the non-oil and gas sector. One of the sectors in the GRDP that is one part of the tourism industry is West Sumatra is one of the provinces that have potential in the field of tourism. And If you look at the West Sumatra Province's GRDP, the growth rate of the accommodation and food and beverage sector is the second highest growth rate in the West Sumatra Province's GRDP of 8.11%. The development of tourism through this sector in West Sumatra is inseparable from the contribution of each Regency / Municipality. Therefore, see the importance of the position of this sector in each Regency / Municipality with the Location Quotient (LQ) Approach. Regency / Municipality in West Sumatra consist of one Municipality which is a leading sector, Six Municipality which are potential sectors, Four Regencies which are developing sectors and Eight Regencies which are lagging sectors for the accommodation and food and beverage supply sector.